Pengaruh Edukasi Kesehatan Berbasis Pendekatan Health Belief Model (HBM) terhadap Peningkatan Motivasi Minum Obat pada Pasien TB Paru di Kelurahan Sindangsari - St. Nurhaifa Alkhoiriyah; Erna Safariyah; Hendri Hadiyanto (Lembaga Pengembangan Kinerja Dosen, 2026)
Pulmonary tuberculosis remains a major public health problem, with medication non-adherence being a key challenge in achieving optimal treatment outcomes. Low motivation to take medication regularly increases the risk of treatment failure and drug resistance. This study aimed to analyze the effect of health education based on the Health Belief Model (HBM) on improving medication-taking motivation among pulmonary tuberculosis patients. A quantitative pre-experimental study with a one-group pretest–posttest design was conducted at Cikundul Public Health Center from October 2025 to January 2026. The study involved 15 pulmonary tuberculosis patients selected using total sampling. Data were collected using a validated and reliable motivation questionnaire administered before and after HBM-based health education. Data analysis included univariate analysis and bivariate analysis using the Wilcoxon Signed Rank Test. The results showed a significant increase in patients’ motivation to take medication after the intervention, with all respondents reaching a good motivation level in the posttest. Statistical analysis revealed a significant difference between pretest and posttest motivation scores (p < 0.001). These findings indicate that HBM-based health education has a significant positive effect on improving medication-taking motivation among pulmonary tuberculosis patients. The study implies that integrating HBM-based educational interventions into routine tuberculosis care may enhance treatment adherence and support the success of tuberculosis control programs.